Moinho Melatti : patrimônio industrial em busca de reconhecimento - Fagundes Varela, RS - Fensterseifer, Margit Arnold (My University, 2024)
This study was developed within the Professional Graduate Program in History of the University of Caxias do Sul, Cultural Heritage, Heritage Education and History Teaching line. The thesis has as its validated product the registration of the Melatti Mill Inventory with Decree-Law 2048, of July 3, 2024, State of Rio Grande do Sul, Fagundes Varela. For this purpose, Melatti Mill is registered with the data collection because the building is an industrial historical heritage and did not have municipal legal protection. The mill is in the possession of Egydio Melatti's family, who keep it complete with the machinery of the grain milling process, even without operation since 2012. For the theoretical contribution, the conceptualizations of the theme of historical-cultural heritage and especially of the industrial heritage are presented, based in particular on the letters of Nitzny Tagil, Dublin and Seville. The methodologies used for historical and technical surveys are also described. The safeguarding of heritage also occurs through the attribution of values that the community recognizes, so the relevant aspects of valuation are described. For the narrative of the history of the Mill, existing documents, photos and equipment are analyzed. For a better understanding of the family history and processes, information collected in the various interviews with Melatti family and relatives is brought. In the analysis of the place and its surroundings, specific methodologies are used that bring characteristic features of the occupation. The following are the constructive characteristics, the milling processes (corn, wheat and rice) with their machinery. The environments that exist in closed and open spaces are also presented. In the analysis of municipal laws, it is clear that the Mill is not inventoried and that there are some listed properties. Convincing the family to inventory the Mill requires a theoretical explanation of what a public interest inventory is and a declaration of historical interest process. In order to organize the collected data, three completed forms are presented for inventory at the municipal level, at the state level, and a copy of a file from the municipal government of Bento Gonçalves whose law decree of 2016 was prepared based on the master's thesis of this author. At the end of the research, the main forms of restoration and requalification are suggested, based on the main patrimonial letters, IPHAN technical notebooks and the guidelines addressed by Doctor and Professor Beatriz Kühl. This set of actions results in the request and consequent approval of the inventory of municipal interest of Melatti Mill, with the future intention of listing this building at the national level. [resumo fornecido pelo autor]
O presente estudo foi desenvolvido junto ao Programa de Pós-graduação Profissional em História da Universidade de Caxias do Sul, linha Patrimônio Cultural, Educação Patrimonial e Ensino de História. A tese tem como produto validado o registro do Inventário do Moinho Melatti com o Decreto-Lei 2048, de 3 de julho de 2024, Estado do Rio Grande do Sul, Cidade de Fagundes Varela. Para tanto realizase um fichamento do Moinho Melatti com o levantamento de dados pois a edificação é um patrimônio industrial e não possuía proteção legal municipal. O moinho está em posse da família de Egydio Melatti que o conserva completo com os maquinários do processo de moagem de grãos, mesmo sem funcionamento desde o ano de 2012. Para o aporte teórico são apresentadas as conceituações da temática de patrimônio cultural e em especial do industrial, alicerçados em especial nas cartas de Nitzny Tagil, Dublin e Sevilha. Também estão descritas as metodologias utilizadas para os levantamentos históricos e técnicos. A salvaguarda dos patrimônios ocorre também pela atribuição de valores que a comunidade reconhece, por isso são descritos os aspectos relevantes de valoração. Para a narrativa da história do Moinho são analisados documentos, fotos e equipamentos existentes. Para o melhor entendimento da história da família e dos processos traz-se informações coletadas nas diversas entrevistas com a família Melatti e os parentes. Na análise do local e seu entorno são utilizadas metodologias específicas que trazem traços característicos da ocupação. A seguir, são apresentadas as características construtivas, os processos de moagem (milho, trigo e arroz) com seus maquinários. Também se apresentam os ambientes que existem nos espaços fechados e abertos. Na análise das leis municipais percebe-se que o Moinho não está inventariado e que existem alguns imóveis tombados. O convencimento da família para inventariar o Moinho exige uma explicação teórica do que é um inventário de interesse público e um processo de tombamento. A fim de organizar os dados coletados são apresentadas três fichas preenchidas para inventário a nível municipal, a nível estadual e um exemplar de fichamento da prefeitura municipal de Bento Gonçalves cujo decreto lei de 2016 foi elaborado com base na dissertação de mestrado desta autora. Finalizando a pesquisa são sugeridas as principais formas de restauro e de requalificação, baseadas nas principais cartas patrimoniais, nos cadernos técnicos do IPHAN e nas diretrizes abordadas pela Doutora e Professora Beatriz Kühl. Este conjunto de ações resulta na solicitação e consequente aprovação do inventário de interesse municipal do Moinho Melatti, com a intenção futura do tombamento a nível nacional desta edificação. [resumo fornecido pelo autor]
Keywords: Fagundes Varela (RS) - História; História - Estudo e ensino; Patrimônio cultural; Fagundes Varela (Brazil) - History; History - Study and teaching; Cultural property